PENGARUH MODEL PEMBELAJARAN DEEP LEARNING TERHADAP HASIL BELAJAR EKONOMI SISWA KELAS X DI SMA PEMBANGUNAN NASIONAL PAGAR MERBAU PEMNAS - Fransiska Dewi, Fajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine and analyze the effect of the Deep Learning model on the economics learning outcomes of Grade X students at SMA Pembangunan Nasional Pagar Merbau (PEMNAS) during the 2025/2026 academic year. The study employs a quantitative approach using a quasi-experimental design, specifically the Nonequivalent Control Group Design. The population consists of all Grade X students at the school, comprising two classes with a total of 60 students. A total sampling technique was used, designating Class X-1 (30 students) as the experimental group applying the Deep Learning model and Class X-2 (30 students) as the control group applying the conventional learning model. Data were collected using economics learning outcome instruments specifically pre-tests and post-tests that met validity and reliability requirements. Data analysis techniques included simple linear regression analysis, the t-test (partial test), and the calculation of the coefficient of determination (R²). The results indicate that the average post-test score in the experimental class (78.27) showed a significantly greater increase compared to the average pre-test score (60.80), with a gain of 17.47 points; meanwhile, the control class saw an increase from an average pre-test score of 61.60 to an average post-test score of 71.73, a gain of 10.13 points. Simple linear regression analysis yielded the equation Y = 48.79 + 0.485X. Hypothesis testing via the t-test resulted in a calculated t-value of 4.693 (or 5.76 in manual calculation), which exceeds the t-table value of 1.701 at a significance level of α = 0.05 and degrees of freedom (df) of 28 (p = 0.000 < 0.05). These findings indicate that the null hypothesis (H₀) is rejected and the alternative hypothesis (Hₐ) is accepted. Furthermore, the coefficient of determination (R-squared) value of 0.440 indicates that the implementation of the Deep Learning instructional model contributes 44% to the improvement of students' economics learning outcomes, while the remaining 56% is influenced by other internal and external factors. Thus, it can be concluded that the implementation of the Deep Learning instructional model has a positive and significant effect on the economics learning outcomes of Grade X students at SMA Pembangunan Nasional Pagar Merbau (PEMNAS).